2011
DOI: 10.4066/amj.2011.723
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of diarrhoea and acute respiratory infection among under-fives in Uganda

Abstract: Policy interventions should target female education, eliminate location and regional disadvantages, and educate the population to adopt breastfeeding practices recommended by the World Health Organization (WHO). The government should also ensure proper dwelling places for the population that are associated with favourable health outcomes. Other proper feeding practices together with breastfeeding (after six months), should be made known to the masses so as to reduce the number of children that are malnourished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

25
60
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 7 publications
25
60
5
Order By: Relevance
“…The odds of diarrhea were higher among rural children than urban ones and this was consistent with the findings in Uganda [11] and Egypt [19]. This could be attributed to the fact that the lack of access to water and sanitation facilities in the rural areas was more than in the urban areas [32].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The odds of diarrhea were higher among rural children than urban ones and this was consistent with the findings in Uganda [11] and Egypt [19]. This could be attributed to the fact that the lack of access to water and sanitation facilities in the rural areas was more than in the urban areas [32].…”
Section: Discussionsupporting
confidence: 86%
“…Epidemiologic studies show that factors determining the occurrence of diarrhea in children are complex and the relative contribution of each factor varies as a function of interaction between socio-economic, environmental and behavioral variables [5,[9][10][11]. Recent research indicated that studies in differing environment and prioritizing interventions based on context would be useful to prevent deaths from diarrhea [12].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with a previous study (Siziya, Muula, & Rudatsikira, 2009), boys" risks of experiencing ARI is higher compared to that of girls (OR = 1.06). While the younger the children are, the more likely the experience of ARI is (Amugsi et al, 2015;Bbaale, 2011). We also observed this kind of relationship.…”
Section: Discussionsupporting
confidence: 77%
“…Existing literature suggests that younger children are more likely to experience infectious diseases than older cohorts, and consequently, a higher proportion of diarrhoea and pneumonia-related deaths happen in the first 2 years of life. [7][8][9] Due to differentials in food intake, standard of living and availability of healthcare facilities, urban-rural variations Open Access are also evident in childhood morbidity. 10 11 Educated mothers are knowledgeable about healthy environments and possible risks of their children being exposed to infectious diseases, and hence, occurrence of infectious diseases is significantly associated with the educational status of mother.…”
Section: Introductionmentioning
confidence: 99%